Pertanggungjawaban KPU Terhadap Penggunaan Sirekap Pada Pemilu Serentak 2024 - Harun, Daeng; Djafar, Marwan; Pede, Albert (Fakultas Hukum Universitas Ichsan Gorontalo, 2024)
Abstract: The purpose of this study is to determine and evaluate the form of KPU's responsibility for the use of sirekap in the 2024 Election. The research method used in this research is the normative research method by taking a statutory approach. The findings or results of this study are in the form of many mistakes that occurred in the 2024 election process due to sirekap, as for the findings, namely the Association for Elections and Democracy (Perludem) Foundation received complaints regarding the use of Sirekap which could not be accessed and could not even be used on voting day. This situation forced KPPS officers to upload C results to Google Drive, while the number of valid votes at polling stations was higher than the number of voters per polling station. Under these conditions, every upload of voting results by KPPS must go through a verification process before being displayed in the election results diagram on the KPU website. However, due to the accumulation of unverified data, some data was hampered to be displayed, so the KPU closed the temporary election result diagram on the day of the recapitulation. The issue of using Sirekap was also discussed in the election result dispute hearing held at the Constitutional Court. Sirekap mobile takes data from the C1 form. The results are made by handwriting using Optical Character Recognition (OCR) technology, but the writing on the C1 form which is handwritten by KPPS members at 822 thousand polling stations is difficult to read by OCR. The camera aspect is also a factor, because Sirekap mobile is installed on each KPPS mobile phone (hp) with different brand quality, so there are differences in the uploaded C1 form; some are clear, dim, white, or yellowish. In addition, folded paper can also cause misinterpretation by OCR.